"Cocktail" of xenobiotics at human relevant levels reshapes the gut bacterial metabolome in a species-specific manner - Zhang, Yingdan (2020)
The human gut microbiome experiences long-term exposure to numerous organic contaminants (e.g., xenobiotics) in the digestive tract, and the possible consequences have rarely been characterized. To date, very few studies have investigated the metabolic variation from different species of gut bacteria in response to xenobiotic mixtures. In this study, we applied liquid chromatography mass spectrometry-based global metabolomics, coupled with targeted metabolomics, to characterize the model gut bacterial responses toward the xenobiotic mixture, covering diverse classes of compounds at human relevant concentrations. The xenobiotic "cocktail" will not likely affect the growth or morphological properties of model bacteria at human relevant concentrations. However, the metabolic results were distinct between four model bacteria and dose levels, showing species-specific and dose-dependent responsive patterns among different commensal gut bacteria. The key metabolites responsive to xenobiotic exposure are mainly involved in amino acid metabolism and central carbon metabolism, including sulfur-containing amino acids, aromatic amino acids, amino sugars, neurotransmitters, and energy-related metabolic pathways. Many of those metabolites also play an important role in the host's health. In summary, our results show that the gut microbiome can be significantly perturbed by exposure to xenobiotic mixtures at human relevant levels, providing key information on susceptibilities of individuals with diverse gut microbial structures.